Lower Face Asymmetry: Can We Distract the Mandibular Lower Border?. Issue 4 (December 2015) - Rao, Santhosh; Rao, Sruthi
Orthognathic surgery and alloplastic grafting are the main stay in management in hemifacial microsomia. Distraction osteogenesis is used to increase the ramus and corpus length in the management, but here we have described a technique to increase the height of the body of the mandible using the principles of basal osteotomy and distraction osteogenesis.